Pembuatan Film Pendek Fiksi Thriller Penggambaran Dibalik Pikiran Penderita Psikotik - Sutikno; Rizqi Rhesa Harsana; Sigit Prayitno Yosep (Universitas Dinamika, 2025)
Mental health is a vital aspect of achieving overall well-being, yet it is often overlooked, especially in developing countries. The focus on mental disorders is dominant over efforts to maintain mental health. Psychosis, such as that experienced by those with psychotic disorders, presents a serious challenge. Its causes are complex, involving genetic factors, brain development, and exposure to stress. Cry of Fear, a video game, provides a narrative around mental health and psychosis, inspiring the author to create a short film with a similar theme. As director, the author details his creative process, choosing the color blue as a symbol of strength and coolness. The short film aims to raise awareness of mental health as a significant issue and reinvents the Cry of Fear narrative in the thriller genre through a unique storytelling style. The filmmaking process also highlights the director's role as creator and leader, bringing imagination to life through images and visuals. The end result is expected to provide an engaging experience for the audience while conveying an important message about mental health.